Modern approach to the choice of laxative agent in surgical interventions in outpatient coloproctology - B. M. Belik; A. N. Kovalev (Амбулаторная хирургия)
Introduction. Elimination of manifestations of functional constipation and normalization of the stool to date remain a complex and finally unresolved problem during typical surgical interventions in outpatient coloproctology.Aim. To evaluate the clinical efficacy of the laxative agent sodium picosulfate in the surgical treatment of non-tumor diseases of the anal canal and rectum in outpatient settings.Materials and methods. The results of surgical treatment of 566 patients with non-tumor diseases of the anal canal and rectum, which were divided into two groups, were analyzed. In 275 patients (group 1), laxative agents were not used during treatment or were used indiscriminately. In 291 patients (group 2), the laxative agent sodium picosulfate was used to normalize colon emptying and soften stools during treatment. Comparison criteria: level of pain syndrome after surgery, degree of inflammatory manifestations in the field of surgical intervention, shape, and nature of fecal masses (based on the Bristol scale), frequency of wound inflammatory complications and recovery time for patients.Results. In the early stages after surgery, the stool had a softened consistency (type 5 and 6) in a much larger number of group 2 patients (89.7 ± 4.1 – 94.2 ± 5.1%) compared with group 1 patients (67.3 ± 4.8 – 76.7 ± 4.9%). At the same time, in group 2 patients, pain syndrome was less pronounced, inflammatory manifestations in the area of surgical intervention regressed faster, incidence of wound inflammatory complications decreased 2.8 times (from 16.4 to 5.8%) and work capacity was recovered earlier than in group 1 patients.Conclusion. The use of the laxative agent sodium picosulfate in coloproctological patients when performing typical surgical interventions on the rectum and anal canal on an outpatient basis eliminates the manifestations of symptomatic constipation, ensures the formation of a softened stool in perioperative periods, reduces mechanical injury to the mucous membrane of the rectum by feces, reduces the level of pain syndrome, which improves the results of surgical treatment by reducing the number of wound inflammatory complications.